ChemInform Abstract: Layered Hybrid Selenoantimonates with Reduced Thermal Conductivity. Issue 13 (18th March 2013) - Chen, Yu‐Chu; Yao, Hongbin; Thiagarajan, Suraj; Wu, Min; Emge, Thomas J.; Yang, Ronggui; Yu, Shuhong; Li, Jing
Abstract The new compounds (III), (VI), and (VIII) are characterized by single crystal XRD, UV/VIS diffuse reflectance spectroscopy, and thermal property measurements.